Medium and large-sized mammals in montane habitats of Oaxaca, México - Ramírez-Bautista, Arturo; Lavariega, Mario C. (Therya Notes, 2021)
Local inventories constitute the baseline to understand the distribution of species and the ecological and historical processes underlay. Such information, in association with the documentation of motivations for hunting, is needed to design long-term conservation strategies. This study provides novel data on medium and large-sized species for the Cerro Piedra Larga (CPL), an interior mountain massif located in Oaxaca, México. We obtained data from direct observations in transects, seeking for indirect evidence, and camera-trapping in tropical dry forest, dry oak-pine forest, and mesic oak-pine. We recorded the hunting motivations of mammals by local people through informal interviews. We quantified the number of species and identified those that are in some category of risk to its conservation. We report the presence of 26 medium and large-sized species in the CPL. Seven species are in some category of risk. Local people recognized 23 species, of which 14 are hunted to prevent damage to domestic animals and crops. Five species are hunted for consumption as bushmeat. Direct observations, camera-trapping, and interviews were complementary methods for improving the species checklist. Seven species constitute the first records for the entire subprovince. The record of Cuniculus paca represents a range extension to central-south Oaxaca. Considering the small, flying, and medium and large-sized mammals, the CPL has 24.9 % of the total terrestrial mammals recorded in Oaxaca. This study highlights the importance of this mountain massif by its diversity of mammals, which is under threat because of slash-and-burn agriculture and road development.